Effect of sodium caseinate and whey protein isolate fortification on the physical properties and microstructure of corn milk yogurt - Supavititpatana P. (2014)
The aim of this research was to investigate the impact of sodium caseinate and whey protein isolate (WPI) fortification on the physical properties and microstructure of corn milk yogurt. The addition of sodium caseinate and/or WPI enhanced lactic acid production and counts of Streptococcus thermophilus and Lactobacillus bulgaricus. The hardnesss, adhesiveness, gumminess, lightness, water holding capacity, consistency and whey drainage increased whereas syneresis and yellow color decreased at higher concentrations of milk proteins. The optimal milk protein addition for improving the physical properties and texture of corn milk yogurt was 4% (w/v) of sodium caseinate.